Pediatric Rhinoplasty: A national surgical quality improvement program analysis. (16th October 2018) - Kamil, Rebecca J.; Roxbury, Christopher; Boss, Emily
Abstract : Objectives: Rhinoplasty is commonly performed in children with congenital anomalies and resultant nasal deformity causing airway obstruction. Little is known regarding patient factors or perioperative sequelae. We define demographic characteristics and perioperative complications for children undergoing rhinoplasty within a large national cohort. Study Design: Retrospective cohort study of children aged ≤ 18 years undergoing rhinoplasty utilizing data from the 2012 to 2015 American College of Surgeons National Surgery Quality Improvement Program‐Pediatric public use file. Methods: All children who underwent rhinoplasty were identified. Postoperative complications were defined as 30‐day postoperative infection, unplanned readmission and reoperation, and death. Multivariate logistic regression was used to identify predictors of complications. Subgroup analysis was performed based on child age (age < 5 years vs. 5–13 years vs. ≥ 14 years). Results: Of 1, 378 children undergoing rhinoplasty, 21(1.52%) children experienced complications, with the most common being unplanned readmission. Younger children were more likely to experience complications (3.79% aged < 5 years vs. 0.66% aged ≥ 14 years; P  = 0.001). Using multivariate logistic regression analysis, we observed a 61% decreased odds of complication with each age group (odds ratio 0.39, 95% confidence interval 0.19, 0.77; P  = 0.007). Younger children were more likely to be male (56.2% male aged < 5 years vs. 46.6% male aged ≥ 14 years; P  = 0.011), have developmental delay (11.7% aged < 5 years vs. 3.65% aged ≥ 14 years; P  < 0.001), and have craniofacial abnormalities (73.2% aged < 5 years vs. 42.1% aged ≥ 14 years; P  < 0.001). Conclusion: Children undergoing rhinoplasty experience few major complications, with the most common being unplanned readmission. Younger children are at greater risk and are more likely to be male with craniofacial abnormalities. Level of Evidence: 4 Laryngoscope, 129:494–499, 2019